CONFLICT BETWEEN MANAGERIAL PREROGATIVE AND EMPLOYEES’ PROTECTION IN MALAYSIA: LEGAL PERSPECTIVE ON RETRENCHMENT AND DISMISSAL - Md Saman, Mazura; Yusof, Salma; Taib, Khairul Nizam (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Workplace governance in Malaysia is characterized by a persistent tension between managerial prerogatives and statutory employee protections. While employers retain the authority to restructure operations, retrench staff, and determine employment terms, these powers must operate within the bounds of procedural fairness, transparency, and good faith. This study aims to examine the legal boundaries of managerial prerogatives in Malaysia, with a specific focus on retrenchment and dismissal. It determines how effectively the law balances operational autonomy with employee protection. Using a qualitative doctrinal methodology, the research analyzes statutory provisions, judicial precedents, and industrial guidelines to assess the extent to which the Employment Act 1955, the Industrial Relations Act 1967, and the Code of Conduct for Industrial Harmony safeguard against arbitrary or unfair dismissals. The findings confirm that while the legislative framework and judicial oversight provide important protections, enforcement gaps and inconsistent procedural application undermine their effectiveness. The study achieves its objective by clarifying the doctrinal limits of employer discretion and contributes to both theory and practice by offering guidance for consistent application of labor laws, thereby promoting a more equitable and sustainable employment environment in Malaysia.